2011
DOI: 10.5539/jas.v3n2p73
|View full text |Cite
|
Sign up to set email alerts
|

Seed Chlorophyll Influences Vigor in Oilseed Rape (Brassica napus L. var AC Excel.)

Abstract: Seeds of Brassica napus L. var AC Excel were sorted into four subsamples on the basis of the amount of chlorophyll present. Vigor of the four subsamples was studied and compared using the germination test, accelerated aging test, controlled deterioration test and electrical conductivity test. Laboratory vigor ratings were correlated with field data. Results show that seed chlorophyll had no significant effect on germination. However, seedling growth and performance were negatively affected by high chlorophyll.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…The statistical analysis showed an important correlation between the 1,000-seed weight and the chlorophyll content in seeds. It was observed that with an increasing 1,000-seed weight, the content of chlorophyll pigments decreased, a finding which is in agreement with Onyilagha et al [38] and Jalink et al [49] The seed dimensions (estimated by the length, width and the equivalent diameter) gradually increased from the green stage of seed maturity to the technical stage, to reach a similar level in the full maturity stage ( Table 2). No detailed research concerning the physical properties of rapeseeds during its development has been reported.…”
Section: Size and Shape Of Rapeseedssupporting
confidence: 87%
See 2 more Smart Citations
“…The statistical analysis showed an important correlation between the 1,000-seed weight and the chlorophyll content in seeds. It was observed that with an increasing 1,000-seed weight, the content of chlorophyll pigments decreased, a finding which is in agreement with Onyilagha et al [38] and Jalink et al [49] The seed dimensions (estimated by the length, width and the equivalent diameter) gradually increased from the green stage of seed maturity to the technical stage, to reach a similar level in the full maturity stage ( Table 2). No detailed research concerning the physical properties of rapeseeds during its development has been reported.…”
Section: Size and Shape Of Rapeseedssupporting
confidence: 87%
“…Moreover, those authors observed that the content of these compounds in the embryo axis was 5-fold higher than in the seed coat. Onyilagha et al, [38] analysing the influence of seed chlorophyll on vigour in oilseed rape, observed that the conducted germination test had suggested that under favourable environmental conditions, the content of chlorophylls in seeds might have no significant effect on germination. However, under any environmental stress, the germination of rapeseeds characterised by high amounts of chlorophylls might be impaired.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only one of them, namely BnPaO 2 , is expressed during maturation of seeds. Remarkably, a low temperature treatment at 0–5 °C leads to disruption of the PaO-dependent chlorophyll degradation pathway and accumulation of so-called “residual” chlorophylls in mature seeds [ 14 , 15 , 19 , 59 , 62 ]. At the terminal stages of the chlorophyll catabolism, RCC is reduced by the C20-C1 double bond of the macrocycle, and an uncolored primary fluorescent chlorophyll catabolite (pFCC, Figure 2 ) with a strong blue fluorescence is formed.…”
Section: Catabolism Of Chlorophylls In Plantsmentioning
confidence: 99%
“…It is important to note, that residual chlorophylls present in physiologically mature seeds and not affecting their germination under optimal environmental conditions, reduce the tolerance of seeds to environmental stress [ 14 , 17 , 18 , 101 ]. Therefore, the standard quality assessment protocols established by breeders often include fluorescence analysis of seed chlorophyll contents [ 17 , 18 , 62 ]. On the physiological level, reduced stress tolerance of chlorophyll-containing seeds is associated with membrane damage and compromised integrity of seed coat, to some extent, associated with insufficient activity of plant antioxidant systems, i.e., the oxidative stress, developing in green seeds, overwhelms defense capacities of the plant organism [ 3 ].…”
Section: Residual Chlorophylls In Mature Seeds: the Problem Of ”Grmentioning
confidence: 99%